The Analysis Performance of a Grid-Connected 8.2 kWp Photovoltaic System in the Patagonia Region - Vidal Gutierrez, Humberto Ricardo; Rivera, Marco; Wheeler, Patrick; Vicencio, Nicolas (My University, 2020)
Solar PV structures for locations at high latitudes in the Northern and Southern Hemispheres are increasingly in the spotlight. The work reported in this paper analyses the behaviour of a grid-connected 8.2 kWp photovoltaic system to either feed on-site electrical loads (a public institution, Corporacion Nacional Forestal (CONAF), located 5.5 km south of Punta Arenas, lat. 53 degrees S) or to feed into the electrical grid when the photovoltaic system generation is higher than the on-site load demand. The system simulation uses the PVSyst software with Meteonorm derived and measured climate information sets (ambient temperature, solar irradiation and wind speed). The agreement between the simulated and measured energy yield is analysed including the evaluation of the optimal generation energy of the PV array, the energy that is fed into the network, the performance ratio, and the normalised energy generation per installed kWp. The PV system considered in this work generates 7005.3 kWh/year, out of which only 6778 kWh/year are injected into the grid. The measured annual performance ratio is around 89%. The normalised productions of the inverter output or final system yield, i.e., useful energy, is 3.6 kWh/kWp/day. The measured annual average capacity factor obtained from this study is 15.1%. These performance parameters will encourage greater use of photovoltaic technology in the Chilean Patagonia region.
Keywords: photovoltaic system; solar energy; grid connected; pvsyst software